Pengaruh Kesejahteraan Sosial Terhadap Agresivitas Siswa Kelas VII SMP Negeri 1 Kepanjen - Kolis Dewi Kurnia; Esa Nur Wahyuni; Romia Hari Susanti (Universitas Kanjuruhan Malang, 2017)
Aggressiveness is an action intended to injure objects that are subjected physically or verbally to a disposition of frustration or anger. High aggressiveness is influenced by the low social welfare of students, if social welfare is high then aggressive behavior can be avoided. This research that is descriptive and correlational, sampling technique used is random sampling. The results of this study indicate that the social welfare level of grade VII students of SMP Negeri 1 Kepanjen included in the high category as many as 142 people (83,52 %), And for the level of aggressiveness of 70 people (41,17%) included in the low category. In this case it can be said that there is a significant negative relationship between social welfare with the aggressiveness of the seventh grade students of SMP Negeri 1 Kepanjen. The main research findings are significant relationship whit negative direction (r hitung = -0,283 dan r tabel = 0,148 at the level of significance 0,05, r hitung -0,283 > r tabel = 0,148. Thus it can be concluded that the correlation test Product moment results indicate that there is a significant and negative relationship between social welfare with the aggressiveness of the seventh grade students of SMP Negeri 1 Kepanjen. The purpose of negative relationship direction is the higher the value of variable X, then followed by the low variable Y.